Proteins of Bartonella bacilliformis: Candidates for Vaccine Development. (30th August 2015) - Henriquez-Camacho, Cesar; Ventosilla, Palmira; Minnick, Michael F.; Ruiz, Joaquim; Maguiña, Ciro
Abstract : Bartonella bacilliformis is the etiologic agent of Carrión's disease or Oroya fever. B. bacilliformis infection represents an interesting model of human host specificity. The notable differences in clinical presentations of Carrión's disease suggest complex adaptations by the bacterium to the human host, with the overall objectives of persistence, maintenance of a reservoir state for vectorial transmission, and immune evasion. These events include a multitude of biochemical and genetic mechanisms involving both bacterial and host proteins. This review focuses on proteins involved in interactions between B. bacilliformis and the human host. Some of them (e.g., flagellin, Brps, IalB, FtsZ, Hbp/Pap31, and other outer membrane proteins) are potential protein antigen candidates for a synthetic vaccine.